Constructing public-private partnerships to undermine the public interest: critical discourse analysis of Working Together published by the International Alliance for Responsible Drinking - Mary Madden; Andrew Bartlett; Jim McCambridge (BMC, 2023)
Abstract Background The global burden of alcohol harm has increased and is forecast to grow further without effective policy implementation. Public-private partnerships aiming to address global health, and other societal challenges, are a burgeoning feature of neoliberal governance. Rhetorically distancing themselves from tobacco, the major alcohol companies are committed to tackling 'harmful drinking' and have created a distinct type of public relations organization for this purpose. The activities of such organizations are increasingly recognized as an impediment to the implementation of policies to reduce alcohol harm, including in low- and middle-income countries where markets are expanding. Methods The approach of critical discourse analysis is used to examine the discursive tactics and strategies used in Working Together; a 'toolkit' published by the key global level alcohol industry public relations organization, the International Alliance for Responsible Drinking (IARD). This study considers how it works discursively to set the terms of, and overcome skepticism about partnerships, to define aims and position various actors by constructing their roles. The construction of prospective partners provides insights into the alcohol industry itself. Results The toolkit operates as an ideological resource for forming public-private partnerships across the world based on the accumulated know-how of the major companies through IARD. This allows the largest alcohol companies to exercise leadership of the industry, while remaining off-stage. The toolkit relies on a form of rhetorical work which creates distance from obvious corporate interests and the harms caused to population health and society. This is accomplished by working against evidence-informed population level approaches, and thus avoiding policies that will make any significant difference to overall alcohol harm. Unspecific "complexity" affords opportunity for preferred types of "actions", and "partnership" provides opportunity to gain credibility by association, further minimizing the likelihood of any material harm being reduced. Conclusions The toolkit is designed to not only legitimate the inclusion of alcohol industry actors as initiating 'partners', but also assigns them roles as managers of a set of carefully constructed relationships. This vision of public-private partnership reproduces the hegemonic narrative that has successfully blocked policy advances for decades and led to growing alcohol harm globally.